2016
DOI: 10.1080/21645515.2015.1107685
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-preventable infections in Systemic Lupus Erythematosus

Abstract: Systemic Lupus Erythematosus (SLE) is characterized by abnormal autoantibody production and clearance. Infections are among the most important causes of morbidity and mortality in SLE patients; they have an increased frequency of severe bacterial and viral infections possibly due to inherited genetic and immunologic defects and to immunosuppressive therapies. In addition, infectious agents can switch on lupus disease expression and activity. Among the strategies to reduce the risk of infection, vaccination can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 112 publications
0
13
0
3
Order By: Relevance
“…After the screening of the title and/or abstract, 8,850 items were discarded. The fulltext of 60 investigations was assessed and 14 texts were excluded with reasons (as reported in Table 2) (21,26,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Finally, 22 articles were included (4 studies had overlapping populations) in the present systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the screening of the title and/or abstract, 8,850 items were discarded. The fulltext of 60 investigations was assessed and 14 texts were excluded with reasons (as reported in Table 2) (21,26,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Finally, 22 articles were included (4 studies had overlapping populations) in the present systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…It should be, however, noticed, that some of these studies are follow-up studies and investigated, at least partially, overlapping patients cohorts. Table 3 provides a list of these redundant investigations (18,21,(37)(38)(39)(40)(41)(42), that have been utilized in the systematic review part but excluded in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Additional concerns that anti-pneumococcal vaccination might worsen disease severity have proven obstructive to enacting guideline recommendations. Although a study of 24 SLE patients showed no significant change in autoantibody titers or C3/C4 serum levels 2 months after anti-pneumococcal vaccination (17), onset of SLE has been described after immunization against tetanus (18, 19), hepatitis B (18, 20), and other vaccines (21), providing cause for concern.…”
Section: Introductionmentioning
confidence: 99%
“…Non-live vaccines such as influenza and pneumococcal vaccines are generally well tolerated in SLE, although they are less immunogenic than in age-matched individuals. 32 Although there is conflicting evidence on whether influenza vaccine exacerbates SLE activity, 33 seasonal influenza vaccination according to national guidelines is recommended. 34,35 Influenza and pneumococcal vaccination is particularly recommended for patients with SLE before rituximab therapy.…”
Section: Vaccinationmentioning
confidence: 99%